Pengalihan kod dalam kalangan pelajar Tamil di Universiti Malaya / Magespari A/P Subramaniam - Subramaniam, Magespari (2012)
This research was carried to study the phenomena related to code switching admist University Malaya undergraduates. The researcher has discovered the rampant use of Bahasa Malaysia and English terms by undergraduates while conversing in Tamil. This act of code switching appears to be done at a sub conscious level. To achieve the objective of this research, the researcher selected 36 samples consisting of University Malaya undergraduates. The conversation of these samples were recorded and analyzed. The researcher collected the data within a six month time frame. In addition to analyzing the data, the researcher also carried out the tasks of observation and interviews to further strengthen the findings of the data analysis. Five of the undergraduates from the selected sample were interviewed to identify the factors that led to the phenomenon of code switching. Thus the study used a mixed method incorporating the qualitative and quantitative research methods. The findings revealed that the phenomenon of code switching in predominant in the conversations of undergraduates tend to use more English terms in their conversations as compared to terms taken from Bahasa Malaysia. An analysis of the terms used, the researcher found that most of them are those of common nouns. The interviewees claimed that code switching using English terms is the trend and it is considered fashionable today.